"Ruminococcus phoceensis, " a new species identified from human stool from an obese patient before bariatric surgery. (November 2016) - Togo, A.H.; Maraninchi, M.; Bittar, F.; Raoult, D.; Million, M.
Abstract: We report here the main characteristics of a new bacterium species, "Ruminococcus phoceensis" strain AT10 (CSUR = P2086, DSM = 100837). This bacterium was isolated from the faeces of a 37-year-old woman from Marseille, France, with morbid obesity before bariatric surgery.